Time-resolved laser fluorescence spectroscopy study of the coordination chemistry of a hydrophilic CHON (1,2,3-Triazol-4-yl)pyridine Ligand with Cm(III) and Eu(III) - Wagner, Christoph; Panak, Petra (Inorganic chemistry, 2017)
The complexation of Cm(III) and Eu(III) with the novel i-SANEX complexing agent 2,6-bis[1-(propan-1-ol)-1,2,3-triazol-4-yl]pyridine (PTD) was studied by time-resolved laser fluorescence spectroscopy (TRLFS). The formation of 1:3, 1:2, and 1:1 metal/ligand complexes was identified upon increasing PTD concentration in 10-3 mol/L HClO4 and in 0.44 mol/L HNO3 solutions. For all these complexes, stability constants were determined at different acid concentrations. Though under the extraction conditions proposed for an An/Ln separation process, that is, for 0.08 mol/L PTD in 0.44 mol/L HNO3, 1:3 complexes represent the major species, a significant fraction of 1:2 complexes was found. This is caused by ligand protonation, and results in lower Eu(III)/Am(III) separation factors compared to SO3-Ph-BTP, until now considered the i-SANEX reference ligand. Focused extraction studies performed at lower proton concentration, where the 1:3 complex is formed exclusively, confirm this assumption.